Update: biological and chemical aspects of Nectandra genus (Lauraceae). Issue 17 (1st October 2016) - Grecco, Simone S.; Lorenzi, Harry; Tempone, Andre G.; Lago, João Henrique G.
Graphical abstract: Abstract: The genus Nectandra, composed by approximately 120 species that are distributed in the tropical and subtropical regions of America, Africa, Asia, and Oceania, belongs to the Lauraceae family. Plants from this genus, usually trees, have been used in folk medicine as anti-inflammatory, analgesic, antifungal and antiprotozoal reagents; its biological potential has been reported in several studies conducted in vitro and in vivo. Chemically, the genus Nectandra contains different types of secondary metabolites, such as alkaloids (aporphine, proaporphine, benzylisoquinoline, bisbenzylisoquinoline, and morphinandienone) and lignoids (furofuran, benzofuran, tetrahydrofuran, dihydrofuran, and 3, 3-neolignan). Other compounds, such as terpenoids (mainly mono and sesquiterpenes), steroids, phenylpropanoids and flavonoids have been described in Nectandra genus. Other minor derivatives such as coumarins, benzoic acid derivatives, xanthone, benzophenones, lactones, sugars and fatty acids have also been isolated. Most of these studies associate biological aspects to isolated compounds. In this review, we provide a comprehensive overview of the chemistry of the genus Nectandra and compile approximately 200 compounds isolated from different species, together with their therapeutic potential.